2012
DOI: 10.1021/cm300407h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Porous Benzimidazole-Linked Polymers and Their Performance in Small Gas Storage and Selective Uptake

Abstract: Porous organic polymers containing nitrogen-rich building units are among the most promising materials for selective CO2 capture and separation which can have a tangible impact on the environment and clean energy applications. Herein we report on the synthesis and characterization of four new porous benzimidazole-linked polymers (BILPs) and evaluate their performance in small gas storage (H2, CH4, CO2) and selective CO2 binding over N2 and CH4. BILPs were synthesized in good yields by the condensation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
405
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(450 citation statements)
references
References 71 publications
42
405
3
Order By: Relevance
“…P-1 still exhibits higher selectivity than P-2 despite its much smaller CO 2 uptake compared to P-2. A similar observation can be made for the PECONF series, 59 the BILP series 44 and a series of aniline hypercrosslinked copolymers. 60 There is oen a trade-off between absolute uptake and selectivity, and the polymers reported above with the highest CO 2 uptake showed lower selectivity than materials with lower uptakes in this series.…”
supporting
confidence: 77%
“…P-1 still exhibits higher selectivity than P-2 despite its much smaller CO 2 uptake compared to P-2. A similar observation can be made for the PECONF series, 59 the BILP series 44 and a series of aniline hypercrosslinked copolymers. 60 There is oen a trade-off between absolute uptake and selectivity, and the polymers reported above with the highest CO 2 uptake showed lower selectivity than materials with lower uptakes in this series.…”
supporting
confidence: 77%
“…comparable to the highest reported pore materials, such as APOP-1-F (43.4 at 273 K) [32], BILP-2 (71 at 298 K) [27] and O-TTPP (50.7, 273K) [12a].…”
Section: Selectivity Of Co 2 /Ch 4 and Co 2 /Nsupporting
confidence: 76%
“…) [25], BILP-10 (38.2 kJ mol À1 ) [26], PECONF-4 (34 kJ mol À1 ) [27], and acidfunctionalized CMP-1-COOH (32.6 kJ mol…”
mentioning
confidence: 99%
“…BILPs exhibited outstanding chemical and thermal properties and excellent CO 2 and H 2 uptakes with high CO 2 /N 2 and CO 2 /CH 4 selectivities. 127 Therefore, it is considered as the most suitable additives for CO 2 separation MMMs. Ali et al incorporated BILP in PIM-1 MMMs and observed significant improvement in permeability of CO 2 with slight decrease in CO 2 /N 2 selectivity up to 30 wt.% loading.…”
Section: Carbon-based MMMmentioning
confidence: 99%